Identifying unique contributions of the coach-athlete working alliance, psychological resilience and perceived stress on athlete burnout among Norwegian junior athletes - Raanes, E. F. W.; Hrozanova, M.; Moen, F. (Sports, 2019)
The main purpose of the current study was to examine how the coach-athlete working alliance, psychological resilience and perceived stress are uniquely associated with burnout among junior athletes in sport. A sample of 670 Norwegian junior athletes practicing a variety of sports participated in the study. A hierarchical multiple regression analysis showed that the bond dimension of the working alliance, the protective factors `planned future` and `structured style`, as well as perceived stress, all contributed uniquely to the explanation of athlete burnout. A dominance analysis identified perceived stress to have the strongest relative influence on athlete burnout among the set of variables investigated in this study. The findings are discussed in terms of applied implications and possible future research.